Investigation on freeform fabrication part orientation and dimensional accuracy - Ong, Justin Lu Chen (2019)
Fine features are important in manufacturing as many applications such as clips and screw boss require it. Fused Deposition Modelling (FDM) machine is the most commonly used Additive Manufacturing (AM) technology, however, due to the material extrusion process, its capability to produce fine features is limited and dimensions will differ when printed in different orientations. To understand the effects of printing angles and improve geometrical accuracy for fine features in FDM, this report investigated the accuracy of negative and positive fine feature when the experiment models were oriented to different printing angles. From the results obtained, detailed inspection and discussion were carried out, followed by measurement and data collation. The data was studied and a mathematical model that forecasts the error of a known dimension and angle was obtained through regression analysis. The forecasted error could be used to offset from the model at the design stage and therefore potentially reduce the geometrical error of fine features.